Scaling and stress dependence of sub-coercive field dynamic hysteresis in 0.6Pb(Zr1/2Ti1/2)O3-0.4Pb(Zn 1/3Nb2/3)O3 ceramic - Yimnirun R. (2014)
The scaling behavior of sub-coercive field dynamic ferroelectric hysteresis under the influence of stress was investigated in rhombohedral 0.6Pb(Zr 0.5Ti0.5)O3-0.4Pb(Zn1/3Nb 2/3)O3 (0.6PZT-0.4PZN) bulk ceramic. The scaling relation of hysteresis area against frequency f, field amplitude E0, and stress σ for the minor loops takes the form of , indicating the difference in the energy dissipation between the stressed and stress-free conditions. While the scaling obtained is very similar to that of soft and hard PZT ceramics, slightly faster responses to f and E0 indicate the ease of polarization orientation in this ceramic with a simpler domain structure compared to commercial PZT ceramics. However, the difference in mechanical properties of these materials could contribute to a variation in the response to stress. While the E0 exponent obtained in this study agreed well with that derived from the Monte Carlo simulation based on the Q-state planar Potts model, the difference in the f exponent obtained experimentally and theoretically was attributed to the depolarizing effects presented in the bulk ceramics. © 2008 IOP Publishing Ltd.